2015
DOI: 10.1039/c5ta03214h
|View full text |Cite
|
Sign up to set email alerts
|

Heterojunctions between amorphous and crystalline niobium oxide with enhanced photoactivity for selective aerobic oxidation of benzylamine to imine under visible light

Abstract: The formation of heterojunctions between two crystals with different band gap structures, acting as a tunnel for the unidirectional transfer of photogenerated charges, is an efficient strategy to enhance the photocatalytic performance of semiconductor photocatalysts. Considering that surface complex photocatalysts also exhibit charge separation and recombination processes, the heterojunctions may also promote the visible-light-response photoactivity of any surface complex catalysts by influencing the transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 63 publications
(96 reference statements)
0
29
0
Order By: Relevance
“…[25][26][27] To our excitement the band structures of Bi 2 WO 6 and Nb 2 O 5 interlaced, 21,25 which is in favour of promoting the separation of the photogenerated carriers, as a result Bi 2 WO 6 will be an appropriate candidate to construct the heterojunction with Nb 2 O 5 . 28 To the best of our knowledge, the Nb 2 O 5 /Bi 2 WO 6 photocatalyst has not been reported.…”
Section: Introductionmentioning
confidence: 96%
“…[25][26][27] To our excitement the band structures of Bi 2 WO 6 and Nb 2 O 5 interlaced, 21,25 which is in favour of promoting the separation of the photogenerated carriers, as a result Bi 2 WO 6 will be an appropriate candidate to construct the heterojunction with Nb 2 O 5 . 28 To the best of our knowledge, the Nb 2 O 5 /Bi 2 WO 6 photocatalyst has not been reported.…”
Section: Introductionmentioning
confidence: 96%
“…With increasing reaction time, the length of these nanopillars increased significantly, and the width of these nanopillars decreased slightly, as depicted in Figure a–d. The amorphous Nb 2 O 5 nanoparticles disappeared and the surface of nanopillars became very smooth, this observation could be attributed to the involvement of ostwald ripening in the growth process, which was a naturally and spontaneously occurring process with minimizing the surface free energy of crystals, and causing the dissolution of smaller particles and further growth of larger crystals. Furthermore, the effect of colloidal activity on the morphology of the product was also investigated, and the results showed that when using the three‐day‐aging Nb colloids as the precursor for the following hydrothermal treatment, the products presented spherical and spindle shapes (Figure e and 3f), rather than the uniform and regular nanopillars morphology before, this may be due to the decrease of colloidal activity after aging.…”
Section: Resultsmentioning
confidence: 98%
“…[49][50][51] Hence all these outstanding results indicate the wide applicability of Nb 2 O 5 @NiFe-MMO rod array for such oxidation reactions with excellent activity and high recyclability. 52 The catalytic performance for the aerobic oxidative coupling of amines over different metal oxides in some literatures is listed in Table S1. † Nb 2 O 5 @NiFe-MMO rod array has higher yields compared to some other metal oxides listed.…”
Section: Resultsmentioning
confidence: 99%